2015
DOI: 10.1002/cbdv.201400269
|View full text |Cite
|
Sign up to set email alerts
|

Lupane‐ and Friedelane‐Type Triterpenoids from Celastrus stylosus

Abstract: Two new triterpenoids, 30-hydroxylup-20(29)-ene 3β-caffeate (1) and 24-nor-friedelan-6α,10-dihydroxy-1,2-dioxo-4,7-dien-29-oic acid (2), together with eight known compounds 3-10, were isolated from the roots of Celastrus stylosus. The structures of these compounds were elucidated on the basis of spectroscopic analyses. To the best of our knowledge, this represents the first study on the chemical constituents of C. stylosus. The antiproliferative activities of the triterpenoids against six human cancer cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…278 Hainanenone A 620, from Drypetes hainanensis, is 23-nor-3-friedelanone 279 and the 24norfriedelane 621 has been found in Celastrus stylosus. 174 Drypetes congestiora is the source of 3a,16b-friedelanediol 622. 280…”
Section: The Lupane Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…278 Hainanenone A 620, from Drypetes hainanensis, is 23-nor-3-friedelanone 279 and the 24norfriedelane 621 has been found in Celastrus stylosus. 174 Drypetes congestiora is the source of 3a,16b-friedelanediol 622. 280…”
Section: The Lupane Groupmentioning
confidence: 99%
“…Nerium indicum, 172 the 4-hydroxy-3-methoxybenzoyl ester 558 from Paullinia pinnata,173 the cafeoyl ester 559 from Celastrus stylosus174 and the 2-benzoyl ester of alphitolic acid from Rubus innominatus175 Hancokinoside, from Allophylus africanus, is the 2-O-b-D-glucopyranoside of the known hancokinol although the diagram in the reference is inaccurate 176. Other lupane saponins with known genins include royleanumioside from Teucrium royleanum177 and a saponin from Cyperus rotundus 178.…”
mentioning
confidence: 99%
“…Biological assay has indicated that the flavonoids, the main constituents of the plant, show a variety of activities, such as topoisomerase II inhibitory, 6 skin whitening, 8 cytotoxic, 9,11 anti-virus 10 and anti-oxidation activities. 14 As part of our ongoing programme exploring medicinal plants, [15][16][17] a new flavanone (1) and three known ones (2-4) (Fig. 1) were isolated from the ethanol extracts of the dried vine stems of S. suberectus.…”
mentioning
confidence: 99%